Molecular typing of cyst-forming nematodes globodera pallida and G.rostochiensis, using real-time PCR and evaluation of five methods for template preparation - Papayiannis, Lambros C.; Christoforou, Michalis; Markou, Yiannis M.; Tsaltas, Dimitrios (My University, 2013)
Globodera pallida and G.rostochiensis are two cyst-forming nematodes known to infest potato crops, causing severe economic losses worldwide. In this study, a real-time TaqMan PCR assay was developed and optimized for the simultaneous detection of G.pallida and G. rostochiensis. The assay's analytical and diagnostic sensitivity and specificity were evaluated using reference isolates. Four different DNA extraction methods and one rapid crude template-preparation procedure were compared in terms of extraction purity, efficiency for PCR applications, utility and cost. Extraction methods A and B included two commercially available kits that utilize silica columns and magnetic beads, respectively. Method C was based on DNA isolation using Chelex resin, and method D was a standard chemistry in-house protocol. Procedure E included the direct use of crude mixture composed of disrupted cysts in Tris-EDTA buffer. The multiplex TaqMan PCR assay successfully discriminated the two nematode species from all reference cyst samples and its recorded diagnostic sensitivity (Dse) and specificity (Dsp) was 100%. On the contrary, in conventional (Co) PCR tests, the overall Dsp and Dse were lower and estimated at 94 and 87% for G. pallida, and 97 and 88% for G. rostochiensis, respectively. Spectrophotometric results showed that DNA extraction methods A, B and C yielded the purest DNA and gave the lowest mean Ct values as well as the most consistent results in Co PCR. Alternative crude preparation method E resulted in statistically similar and Ct values consistent with those obtained with methods A to C when tested by TaqMan PCR. The developed assay, using crude template-preparation E, allows the simple, accurate and cost-effective testing of a large number of cyst samples and can be applied in surveys and certification schemes.
Keywords: DNA extraction; Potato cyst nematodes; Sensitivity; Specificity; TaqMan PCR